The stigma of HIV positive users of the public health system - Garbin, Cléa Adas Saliba; Martins, Ronald Jefferson; Belila, Naiana de Melo; Garbin, Artênio José Ísper (Brazilian Journal of Sexually Transmitted Diseases, 2017)
Introduction: The initial idea of AIDS as a disease that affects individuals with attitudes disapproved by society has caused stigmatization and prejudice among HIV positive individuals. Objective: To analyze the existence of prejudice and discriminatory attitudes of Unified Health System (“Sistema Único de Saúde” – SUS) users towards HIV positive individuals, according to socioeconomic class. Methods: This is a cross-sectional, descriptive research, with quantitative approaches. We categorized the population according to the Brazilian Criterion of Economic Classification, and applied a structured questionnaire related to prejudice, discrimination, and perceptions regarding sterilization and infectious diseases; as well as questions from a relevant Ministry of Health publication. Results: The study population consisted of 150 individuals, 77.3% of which asserted they would agree to be treated immediately after an HIV positive patient and 92% after a prisoner. However, 42% preferred being examined before HIV positive individuals, and 23.3% before a prisoner. The majority reported concern about the sterilization of dental material (98%), though 42% did not know how the procedure was carried out. There was significant difference between individuals who initially said they would not mind being received after HIV positive patients (p=0.0029) or inmates (p<0.0001), and those who later said they would rather be received before individuals in these conditions. There was no association between socioeconomic class and prejudice. Conclusion: SUS users show prejudicial and discriminatory attitudes toward HIV patients, often expressed in subtle manners, regardless of economic class of the individual.